2015
DOI: 10.1097/jpn.0000000000000114
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem Effects of Hypertensive Disorders of Pregnancy

Abstract: Hypertension predisposes the woman and fetus to adverse outcomes during the pregnancy and postpartum. The risk for maternal complications and neonatal morbidity associated with the necessity of preterm birth extends beyond the postpartum and postnatal period. A comprehensive review of the multisystem effects of hypertensive disorders and underlying pathophysiology is provided to support the role of prompt identification of and management of acute complications of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
6
0
1
Order By: Relevance
“…This finding is consistent with studies showing the influence of employment status on preterm birth, small for gestational age and other neonatal outcomes [50, 51]. Finally, we confirmed previous evidence that diabetes, hypertension and to a greater extent pre-eclampsia and drug therapies for managing these concomitant diseases, are leading causes of adverse neonatal outcomes [5257]. …”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with studies showing the influence of employment status on preterm birth, small for gestational age and other neonatal outcomes [50, 51]. Finally, we confirmed previous evidence that diabetes, hypertension and to a greater extent pre-eclampsia and drug therapies for managing these concomitant diseases, are leading causes of adverse neonatal outcomes [5257]. …”
Section: Discussionsupporting
confidence: 93%
“…For the reasons, it may be associated with the attention of HDP in clinical practice, especially the pregnant women of the pre-eclampsia. The physicians would recommend pregnant and fetal monitoring and interference actively in order to prevent the progression of pre-eclampsia [15,16]. Our data indicated that the majority of cases (90%) underwent hormonal therapy to ensure the pulmonary development, which could sharply reduce the possibility of RDS induced by preterm delivery.…”
Section: Discussionmentioning
confidence: 91%
“…After such administration, it's important to monitor for signs of magnesium toxicity, which include bradycardia, bradypnea, oliguria, and altered states of consciousness (such as confusion, anxiety). (Pfaff, 2014;Witcher et al, 2015) Intrapartum phase. In women with mild preeclampsia without signs of clinical instability or indicators for preterm delivery, full-term delivery may be considered.…”
Section: Managementmentioning
confidence: 99%